Streptobacillus moniliformis subdural empyema in a homeless patient. (November 2021) - Roussel-Simonin, Cyril; Jousset, Agnes B.; Knafo, Steven; Bukreyeva, Iryna; Fortineau, Nicolas; Copaciu, Razvan; Escaut, Lélia; Jauréguiberry, Stéphane
Highlights: The social precariousness in which homeless persons live is a medical challenge. A homeless man was diagnosed with empyema due to Streptobacillus moniliformis . MALDI-ToF spectrometry and gene sequencing helps identification. Abstract: Background: Streptobacillus moniliformis, which is transmitted through rodents, is an emerging zoonotic pathogen among homeless persons. Untreated, the disease can persist for weeks or months; mortality rate ranges from 7% to 13% and can be as high as 53% in endocarditis. Case report: We report here the case of a homeless patient with a history of chronic subdural hematoma, who suffered rat's bites on his face. He presented to our hospital with a picture of cerebral empyema due to Streptobacillus moniliformis that occurred through contiguous spread from the superinfected skin lesions due to the rat bite. Given the technical growth difficulties, S. moniliformis was identified through MALDTI-ToF mass spectrometry. The patient was successfully treated with a 6-weeks course of intravenous then oral amoxicillin. Besides the fact that cerebral empyema is an uncommon complication of S. moniliformis infection, this case highlights the usefulness of 16S RNA PCR and mass spectrometry to identify rare bacterium, as well as the possibility of using amoxicillin instead of intra muscular penicillin in S. moniliformis infections. Conclusion: Contact with rats in homeless patients carries a risk of transmission of Streptobacillus moniliformis . Physicians should be aware of this specific exposure and of this zoonotic disease. The microbiology laboratory has to be informed of the suspected diagnosis, given the difficulty of growth of this pathogen.